Effect of Nickel Doping on the physical Properties of Nanostructured Cadmium Oxide Thin Films Synthesized via Chemical Spray Pyrolysis - Taghreed Khalid Hameed (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In this study, the effects of nickel (Ni) doping on the microstructure, morphology, and optical behavior of nanostructured CdO thin films deposited by chemical spray pyrolysis (CSP) are explored. Thin films were synthesized with varying Ni doping concentrations (0%, 1%, and 3%) and deposited on glass substrates. X-ray diffraction analysis revealed a polycrystalline structure in all films with preferential (200) orientation. Nickel doping led to increased crystallite size while reducing both dislocation density and microstrain. AFM images confirmed a uniform, densely packed morphology, with decreased surface roughness and average particle size as Ni content increased. Optical measurements showed that transmittance decreased and absorbance increased with higher Ni doping. The optical band gap exhibited a gradual reduction with higher doping concentrations, which is associated with the creation of localized energy states within the band structure. Additionally, extinction coefficient and refractive index values were affected by doping, demonstrating a decline with increasing Ni concentration. Overall, Nickel doping induces significant changes in the physical behavior of CdO films.